A single-phase white-emitting La(BO3,PO4):Dy3+ phosphor with high thermostability - Song, Ruitong; Zhang, Zhuohui; Li, Hong; Luo, Zhenyu; Yang, Jinyan; Ma, Jie; Xiang, Xianfeng; Zeng, Qing; Zhu, Jing (Ceramics international, 2023)
Developing single-phase white-emitting phosphor has increasingly become an effective strategy to solve the emerging challenges of multiple phosphors-converted white light-emitting diodes such as unavoidable reabsorption, high production cost, and low thermostability. In this work, a single-phase white-emitting La(BO3,PO4):Dy3+ phosphor was synthesized. The photoluminescence performance characterizes the two strong visible emissions of Dy3+: blue (470–500 nm, 4F9/2 → 6H15/2) and yellow lights (570–600 nm, 4F9/2 → 6H13/2). The content quenching of Dy3+ presents at x = 0.03 mol, which is controlled by the dipole–dipole interaction. The optimized product La0.97Dy0.03(BO3,PO4) has a high thermostability. It has also the comparable color coordinates with the ideal white light due to the proper yellow-blue intensity ratio. The above studies confirm that the Dy3+-activated La(BO3,PO4) phosphor could be a prospective white-emitting candidate in lighting application.